2023
DOI: 10.2147/jpr.s410603
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of Research Trends on Tuina Manipulation for Neck Pain Treatment Over the Past 10 Years

Abstract: Tuina is an effective treatment for neck pain (NP). However, there has been no bibliometric analysis of the global application and emerging trends of tuina performed for NP. Therefore, this study aimed to provide an overview of the current state and future trends in the field. Articles about tuina for NP, published from January 1, 2013, to January 1, 2023, were searched in the Web of Science Core Collection database. CiteSpace (6.1.R6) and VOSviewer (1.6.18) software were used to analyze annual trends in liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Through bibliometric analysis of literature on NP treatment over the past decade, significant research gaps and potential duplication issues have been identified. Zhichao Gong conducted a bibliometric analysis of the literature about the treatment of NP using massage manipulation over the past decade, encompassing 505 articles [ 58 ]. Similarly, Jaehyeon Park undertook a review of acupuncture treatment for NP over the past two decades, examining 325 papers [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through bibliometric analysis of literature on NP treatment over the past decade, significant research gaps and potential duplication issues have been identified. Zhichao Gong conducted a bibliometric analysis of the literature about the treatment of NP using massage manipulation over the past decade, encompassing 505 articles [ 58 ]. Similarly, Jaehyeon Park undertook a review of acupuncture treatment for NP over the past two decades, examining 325 papers [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“… 34 The effect of tuina is attributed to relaxing muscles and tendons, improving local blood circulation, decreasing edema and aseptic inflammation. 35 Tuina has been widely used to treat NSCNP worldwide, 36 and the efficacy has also been reported. 37 However, to our knowledge, there have been few clinical studies on the treatment of combining tuina and specific therapeutic neck exercise in NSCNP.…”
Section: Discussionmentioning
confidence: 99%
“…We read with interest an article titled “Bibliometric Analysis of Research Trends on Tuina Manipulation for Neck Pain Treatment Over the Past 10 Years” published in the Journal of Pain Research . 1 Drawing on modern physical therapy background, we aim to contribute some personal perspectives on this article and research on Tuina.…”
Section: Dear Editormentioning
confidence: 99%